Analysis of water performance of coating mortars incorporated with tire rubber - Pagoto, Leticia Martelo [UNESP]; Akasaki, Jorge Luis [UNESP]; Melges, Jose Luiz Pinheiro [UNESP]; Fioriti, Cesar Fabiano [UNESP] (Pontificia Univ Catolica Chile, Dept Ingenieria & Gestion Construccion, 2022)
This paper analyzed the behavior of mixed mortars incorporated with rubber from the tire retreading process, based on partial sand substitution. The content of rubber incorporation in the mortars was 5%, 10%, 15%, and 20% by volume. The different granulometries of rubber were denominated as thick (passed through a sieve # 1.19 mm) and fine (passed through a sieve # 0.60 mm). Tests were performed to evaluate water retention, capillary absorption, drying, immersion absorption, water vapor permeability, and permeability to water under pressure. The results showed that the fine rubber was distinguished by its higher retention of water at the contents of 15% and 20%, lower absorption via both capillary and immersion, higher drying capacity, higher permeability to water vapor, and lower permeability to water under pressure.
Keywords: Coating mortar; Tire rubber; Composites; Behavior in water; Alternative material